Effects of HIP on Microstructure and Mechanical Properties of LMD Fe36Mn21Cr1815NiAl10 High-Entropy Alloy - Gang Wang; Xvteng Lv; Xiangyu Xv; Runbo Zhang (Metals)
To reduce costs, a cobalt-free FeMnCrNi-based HEA has been proposed. Further investigation into the mechanical properties of the Fe36Mn21Cr18Ni15Al10 alloy is essential to expand its application potential. In this study, a cobalt-free Fe36Mn21Cr18Ni15Al10 HEA was fabricated using LMD, and the effects of HIP on its microstructure and mechanical properties were investigated. Results indicated that the as-printed specimen exhibited a dual-phase structure consisting of BCC and FCC phases, with the B2 phase dispersed as fine blocks. After HIP treatment, the content of the FCC phase significantly increased, displaying a lamellar distribution between the BCC phases, with secondary block-like B2 phases forming within the BCC matrix. The HIP process enhanced the density of the high-entropy alloy to 98.2%, while the tensile strength at 25 °C increased to 903.9 MPa. Additionally, the post-fracture elongation improved to 17.4%, thereby increasing the potential for industrial applications of HEAs.